2004
DOI: 10.1093/jnci/djh020
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Glycemic Load and Risk of Colorectal Cancer in the Women's Health Study

Abstract: Although diet is believed to influence colorectal cancer risk, the long-term effects of a diet with a high glycemic load are unclear. The growing recognition that colorectal cancer may be promoted by hyperinsulinemia and insulin resistance suggests that a diet inducing high blood glucose levels and an elevated insulin response may contribute to a metabolic environment conducive to tumor growth. We prospectively followed a cohort of 38 451 women for an average of 7.9 years and identified 174 with incident color… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
112
4
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(125 citation statements)
references
References 18 publications
6
112
4
3
Order By: Relevance
“…This means that under iso-energetic conditions, high-GL diets are lower in fat, protein and alcohol. Although similar results for fat and protein were obtained earlier by Schulz et al (2005), they reported a positive association with alcohol, whereas we, along with others (Salmeron et al, 1997;Michaud et al, 2002;Higginbotham et al, 2004;Schulze et al, 2004), found a negative relationship. However, this may be because of the fact that beer was assigned a hypothesized value of 95 and wine of 61 by Schulz et al (2005), whereas we assigned a communicated value of 66 to beer and no value to wine, and in the other studies no value was assigned to alcoholic beverages.…”
Section: à005supporting
confidence: 88%
“…This means that under iso-energetic conditions, high-GL diets are lower in fat, protein and alcohol. Although similar results for fat and protein were obtained earlier by Schulz et al (2005), they reported a positive association with alcohol, whereas we, along with others (Salmeron et al, 1997;Michaud et al, 2002;Higginbotham et al, 2004;Schulze et al, 2004), found a negative relationship. However, this may be because of the fact that beer was assigned a hypothesized value of 95 and wine of 61 by Schulz et al (2005), whereas we assigned a communicated value of 66 to beer and no value to wine, and in the other studies no value was assigned to alcoholic beverages.…”
Section: à005supporting
confidence: 88%
“…The prospective studies' results have been mixed. Some studies showed increased risk of cancer in the whole cohort with high glycemic load [18-20]; some studies found only increased risk among subgroups such as sedentary, overweight subjects [21-24]; other studies concluded that there was no increased risk for any of their cohort [25-28]. Even though there were no associations between glycemic load and colorectal, breast, or pancreatic cancer in the Nurses' Health Study there was still a strong link between diabetes and colorectal cancer [29].…”
Section: Reviewmentioning
confidence: 99%
“…However, epidemiologic studies currently provide limited support for a direct role of diets high in glycemic load (which takes the total carbohydrate intake into account) in cancer development. Some studies of colon (Terry et al, 2003a) and breast cancer did not find an association between diets high in glycemic load or sugar and cancer, while others did Augustin et al, 2001;Higginbotham et al, 2004). The inconsistencies may result from difficulties in measuring the glycemic potential of diet, given the importance of meal composition, for example.…”
Section: Carbohydratesmentioning
confidence: 99%